Students’ perceptions of using LyricsTraining.com as a pre-listening media to enhance readiness in listening activities - Ramadhan, Bintang; Marlina, Leni (Universitas Negeri Padang, 2025)
This study aimed to investigate EFL students’ perceptions of using LyricsTraining.com as a pre-listening media to enhance readiness in listening activities. A quantitative descriptive design was employed, involving 70 students from SMAN 4 Payakumbuh. Data were collected using a 21-item Likert-scale questionnaire based on the Technology Acceptance Model (TAM), covering three indicators: Perceived Ease of Use (PEOU), Perceived Usefulness (PU), and Attitude Toward Using (ATU). Each item was rated on a four-point scale (1 = strongly disagree to 4 = strongly agree). Descriptive statistical analysis was conducted to calculate the mean scores for each indicator. The results show that students perceive LyricsTraining.com very positively, with mean scores of 3.45 for PEOU, 3.43 for PU, and 3.34 for ATU, all categorized as “very positive.” These findings indicate that the platform is easy to use, useful, and effective in preparing students for classroom listening activities.